Modeling migration of organic pollutants in groundwater — Review of available software. (October 2021) - Pietrzak, Damian
Abstract: The presence of organic pollutants e.g. contaminants of emerging concern (CECs) in aquatic environments has been of great concern worldwide for years. Increasing numbers of different types of CECs detected in the aquatic environment requires action to a detailed understanding of the distribution and transport of these compounds in groundwater, to guarantee safe drinking water for people in the future and sustainable development of the environment. Nowadays, progress in software permits the simulation of organic pollutant transport in the soil-water system using advanced mathematical models. Those models can be applied both to simulate contaminant transport or to calculate values of transport parameters by inversion. This article summarizes the results of literature research regarding the available software for modeling the migration of organic pollutants in groundwater. They were detailed described in terms of their operation, applications, usefulness, advantages, and limitations, along with an indication of the most useful in this subject. Highlights: The presence of organic pollutants in groundwater is a cause for concern worldwide. Different software exist for simulation of organic contaminant migration. Some of them can be used to calculate value of transport parameters of contaminants. The most well-known and useful software are those based on MODFLOW core.